Coming Out in an Alternative World in Marion Zimmer Bradley’s The Heritage of Hastur and Sharra’s Exile (American & British Studies Annual, 2013)
The present article analyzes same-sex relationships as portrayed in Marion Zimmer Bradley’s novels The Heritage of Hastur (1975) and Sharra’s Exile (1981). Both novels belong to the genre of science fantasy (a hybrid of science fiction and fantasy) and are set in the alternative world of Darkover. Yet, despite the opportunities offered by the fantastic genre, the coming out of the novels’ protagonists, Regis Hastur and Danilo Syrtis, is only a thinly veiled version of a coming out in contemporary Western society, bringing together commonplace themes such as the various levels of social acceptance of homosexuality, the strong repression of past experience, child abuse, together with the associated corruption of adults trying to cover it up, and social pressure to marry and preserve an impeccable public image. Even though the author does not offer any radical views on homosexuality in these two novels, from the perspective of gay literature scholarship the novels do expand the ways coming out is treated in literature and may serve as a bridge between readers of realistic fiction and the fantastic genres.
Keywords: American literature; gay literature; coming out; science fiction; fantasy; Marion Zimmer Bradley; The Heritage of Hastur; Sharra’s Exile; Darkover